Morphometric evaluation of caprine spermatozoa by HT-IVOS System at pre-freeze and post-thaw stages of cryopreservation - SUNDARARAMAN, M N; EDWIN, M JOHN (The Indian Journal of Animal Reproduction, 2023)
Semen samples were collected from two adult Boer Grade (Boer x Local) goats by artificial vagina method, evaluated,extended in Tris-Egg yolk-Glycerol based diluent and frozen by French straw technique. After dilution, a portion of extended semenwas further diluted to prepare thin sperm smears. The smears were stained with Stat III, Andrology stain for morphometricevaluation by HT-IVOS system. The frozen samples were thawed and samples showing acceptable sperm motility were furtherdiluted for preparation of semen smears for staining and evaluation by HT-IVOS system (CASA). A total of 1000 spermatozoa eachat pre-freeze and post-thaw stages of cryopreservation, involving 6 different samples each from two bucks were analysed formorphometric traits viz., major axis, minor axis, elongation, head area, perimeter and tail length. Highly significant (P $ 0.01)differences were noticed for most of the morphometric traits except for minor axis of the sperm head and tail length betweendifferent stages of semen processing for cryopreservation. The variations obtained in major axis, minor axis, elongation, head areaand perimeter of the sperm head between bucks were also highly significant (P $ 0.01 ). Most of the morphometric traits of the spermheads of frozen-thawed spermatozoa also exhibited highly significant (P $ 0.01) variation between bucks. Cryopreservation resultedin irreversible changes in structural integrity of caprine spermatozoa.
Keywords: Goat spermatozoa; cryopreservation; morphometry; CASA